The first crystal structure of a DNA-free nuclear receptor DNA binding domain sheds light on DNA-driven allostery in the glucocorticoid receptor - Frank, Filipp (Sci Rep, 2018)
The glucocorticoid receptor (GR) is a steroid hormone receptor of the nuclear receptor family that regulates gene expression in response to glucocorticoid hormone signaling. Interaction with specific GR DNA binding sequences causes conformational changes in the GR DNA binding domain (DBD) that result in recruitment of specific sets of co-regulators that determine transcriptional outcomes. We have solved the crystal structure of GR DBD in its DNA-free state, the first such crystal structure from any nuclear receptor. In contrast to previous NMR structures, this crystal structure reveals that free GR DBD adopts a conformation very similar to DNA-bound states. The lever arm region is the most variable element in the free GR DBD. Molecular dynamics of the free GR DBD as well as GR DBD bound to activating and repressive DNA elements confirm lever arm flexibility in all functional states. Cluster analysis of lever arm conformations during simulations shows that DNA binding and dimerization cause a reduction in the number of conformations sampled by the lever arm. These results reveal that DNA binding and dimerization drive conformational selection in the GR DBD lever arm region and show how DNA allosterically controls GR structure and dynamics.